Improved estimation model and empirical analysis of relationship between agricultural mechanization level and labor demand - Fulin, Wang; Shengxue, Zhao; Xiaoming, Fu (International Journal of Agricultural and Biological Engineering, 2016)
The research on the relationship between mechanization level in planting industry and labor demand was carried out based on the present literatures. The former estimation model of labor demand in planting industry was established without analyzing the effects of planting structure on labor demand in planting industry. The purpose of the research is to develop and perfect the theory of estimating both labor demand and rural surplus labor in planting industry, then to provide some theoretical references for scientific estimation. The model established in this research can be used to calculate not only the amount of current labor demand, but also the demand in the various moment of future according to forecasted mechanization level and cultivated areas. Furthermore, it was explored how to obtain the indexes of cultivated areas, mechanization level and the average cultivated area that each labor can burden when the mechanization level is 0 and 100%. According to statistics principle, the methods of inspection to eliminate abnormal data and data processing were given in order to make the data more credible. Finally, an example was presented for demonstration purposes. Keywords: agricultural mechanization level, planting industry, labor demand, estimation model, data acquisition, crop production DOI: 10.3965/j.ijabe.20160902.2188 Citation: Wang F L, Zhao S X, Fu X M. Improved estimation model and empirical analysis of relationship between agricultural mechanization level and labor demand. Int J Agric & Biol Eng, 2016; 9(2): 48－53.